The species of the bee genus Centris of the “hyptidis group” revisited with the description of Centris (Anisoctenodes) new subgenus (Hymenoptera: Apidae: Centridini) - Vivallo, Felipe (European Journal of Taxonomy, 2020)
In this paper, the species of Centris of the “hyptidis group” are revisited, proposing to recognize them as members of Anisoctenodes subgen. nov., a new subgenus supported by morphological and molecular data. The species included in this new taxon are C. hyptidis Ducke, 1908 (type-species), C. hyptidoides Roig-Alsina, 2000, C. thelyopsis Vivallo & Melo, 2009 and C. anisitsi (Schrottky, 1908), transferring this latter from Centris (Xanthemisia) Moure, 1945. An updated key, information on the type depository, a distribution map, photographs of both sexes as well as of the diagnostic characters of the new subgenus are also provided.